Distribution of aedes mosquitoes in three selected localities in Malaysia - Wan-Norafikah, O; Nazni, W.A; Noramiza, S; Hafa’Ar-Ko’ohar, S.S; Heah, S.K; Nor-Azlina, A.H; Khairul-Asuad, M; Lee, H.L (Universiti Kebangsaan Malaysia, 2012)
Aedes aegypti and Aedes albopictus are the principle dengue vectors in Malaysia. The presence and distribution of Aedes larvae were studied in three different localities in Kelantan, Terengganu and Sabah, Malaysia in October 2008, November 2008 and June 2009. Two hundred (200) ovitraps per locality were placed randomly indoors and outdoors, depending on the environment of each locality. The highest mean number of Ae. aegypti and Ae. albopictus larvae per recovered ovitrap for both indoors and outdoors was obtained from Kg. Paya Rambai, Kelantan. The indoor populations of Ae. aegypti as well as the indoor and outdoor populations of Ae. albopictus in Kg. Paya Rambai, Kelantan were significantly higher than the other two study sites (p<0.05) by 1.03- and 4.67-folds, 2.36- and 5.84-folds and 1.98- and 4.00-folds, respectively. Both Ae. aegypti and Ae. albopictus were also found to breed within the same ovitraps placed indoors and outdoors in all study sites ranging from 15.22% to 31.82% of the total positive ovitraps. This study showed that both species could serve as the vectors of dengue in all study sites as indicated by the high populations recorded. The reliability and sensitivity of ovitraps in Aedes surveillance was also proven